Supporting and Inhibiting Factors in the Implementation of the Kesatria Team in Maintaining Public Order in North Padang District, Padang City - Sari, Melani Fitria Devita; Alhadi, Zikri (The Future of Education Journal, 2026)
Public order constitutes one of the compulsory functions of local governments and requires policies to be implemented in an effective and sustainable manner. The Padang Utara District in Padang City continues to experience persistent public order issues, including the presence of unauthorized street vendors, improper parking practices, and the inappropriate use of public spaces. In response to these challenges, the district government introduced a non-digital policy initiative through the establishment of the Kesatria Team. This study aims to analyze the factors that support and hinder the implementation of the Kesatria Team in maintaining public order in Padang Utara District. The research adopts a descriptive qualitative approach, with data collected through in-depth interviews and document review. The findings reveal that inter-agency coordination, strong leadership commitment, and clearly defined task allocation serve as key supporting factors in policy implementation. Conversely, low levels of public awareness, economic pressures, and limited supporting facilities remain the primary obstacles to effective policy execution.